2023
DOI: 10.1021/acs.biomac.3c00196
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a STING Agonist and Photothermal Therapy Using Chitosan Hydrogels for Cancer Immunotherapy

Abstract: Cyclic dinucleotides (CDNs) are a promising class of immune agonists that trigger the stimulator of interferon genes (STING) to activate both innate and acquired immunity. However, the efficacy of CDNs is limited by drug delivery barriers. Therefore, we developed a combined immunotherapy strategy based on injectable reactive oxygen species (ROS)-responsive hydrogels, which sustainably release 5,6-dimethylxanthenone-4-acetic acid (DMXAA) as known as a STING agonist and indocyanine green (ICG) by utilizing a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…This bioresponsive gel may harness local ROS to facilitate immunotherapy drug release. Thereby improving combination therapy efficacy, modifying the TME, restraining tumor growth, inducing memory immunity, and protecting against tumor rechallenge . In this study, a novel approach for breast cancer treatment has been developed involving gefitinib-loaded cellulose acetate butyrate nanoparticles (Gnb-NPs) loaded in chitosan/β-glycerophosphate hydrogels.…”
Section: Role Of Hydrogels In Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…This bioresponsive gel may harness local ROS to facilitate immunotherapy drug release. Thereby improving combination therapy efficacy, modifying the TME, restraining tumor growth, inducing memory immunity, and protecting against tumor rechallenge . In this study, a novel approach for breast cancer treatment has been developed involving gefitinib-loaded cellulose acetate butyrate nanoparticles (Gnb-NPs) loaded in chitosan/β-glycerophosphate hydrogels.…”
Section: Role Of Hydrogels In Immunotherapymentioning
confidence: 99%
“…Hence, as a result, it concluded that the prepared hydrogel could inhibit the growth of tumors in breast cancer. 192 Chen et al 193 developed an innovative immunotherapy approach utilizing injectable reactive oxygen species (ROS) within responsive hydrogels. These hydrogels sustainably release 5,6-dimethylxanthenone-4-acetic acid (DMXAA), a STING agonist, and indocyanine green (ICG) in response to the high ROS levels in the tumor microenvironment (TME).…”
Section: Role Of Hydrogels In Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation